Mitigation of residential densification in height. The case of Las Condes commune of Santiago de Chile - Pallarés Torres, Maria Eugenia; Pallarés Torres, Mirtha; Lou, Jing Chang (Estoa. Journal of the Faculty of Architecture and Urbanism, 2018)
Residential densification in height is a territorial planning strategy designed to increase the use of the attributes of the urban space that mainly affects the consolidated territories. It is expressed through the change in the urban parameters altering the productivity and occupancy density, the building surfaces and the building height, conditions that together modify the urban landscape generating externalities that must be controlled. Otherwise they cause segregation and loss of identity, so that the inclusion of regulations aimed at mitigating impact is the most appropriate strategy for the installation of the measure. The analysis of the effect caused by the special regulations for residual properties caused by the fusion of soils installed in the Regulatory Plan of the Commune of Las Condes, one of the most important in the city of Santiago, allowed to evaluate the pertinence and to recommend the conditions of improvement and replicability.